DESIGN AND COMPARATIVE EVALUATION OF CLARITHROMYCIN GASTRIC BIOADHESIVE TABLETS BY EX VIVO AND IN VIVO METHODS - Km, Nishad; B, Arul; S, Rajasekaran (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present investigation was to formulate controlled release of mucoadhesive clarithromycin tablets using natural polymers. Methods: Tamarind seed polysaccharide obtained from Tamarindus indica and chitosan act as natural polymers. The formulated tablets of the combined form of thrombospondin (TSP) and chitosan were analyzed by in vitro dissolution method. The optimized formulations were selected for ex vivo and in vivo studies and compared with hydroxypropyl methylcellulose K100 polymer by evaluating gastric retention period by X-ray imaging technique, and drug bioavailability by a pharmacokinetic method from blood samples was determined by high-performance liquid chromatography-mass spectrometry method. Results: The gastric mucoadhesive tablets were prepared using chito-TSP polymers. The in vitro drug release showed good release character for 24 h. The ex vivo studies of tablets showed good adhesive property for a long time. The X-ray imaging technique also proved the adhesive character of tablets. From blood serum sample of rabbits, bioavailability of the drug is in according to the controlled release mechanism. Conclusion: The selected formulations were subjected to stability studies. The study concluded that combination of chitosan and TSP is best natural polymer for mucoadhesion by the advantages of controlled release and biodegradation.